Pegylated Liposomal Doxorubicin in Vindesine-Based and Bortezomib-Based Regimens for Patients With Newly Diagnosed Multiple Myeloma: A Retrospective Study of Efficacy and Safety - Zhai, Yujia; Yuan, Dai; Ge, Xueling; Hu, Shunfeng; Li, Peipei; Fang, Xiaosheng; Li, Ying; Zhou, Xiangxiang; Wang, Xin (Frontiers in Oncology, 2021)
Abstract Purpose：Although pegylated liposomal doxorubicin (PLD) has been approved in combination with bortezomib for relapsed/refractory multiple myeloma (MM), the antitumor efficacy and tolerability of PLD in different regimens for patients with newly diagnosed MM (NDMM) have not been fully defined. Methods: A total of 249 NDMM patients diagnosed between January 2008 and October 2019 were included in this retrospective study. Among them, 112 patients received vindesine-based chemotherapy (35 vDD and 77 vAD) and 137 received bortezomib-based chemotherapy (58 VDD and 79 VD). Results: In bortezomib-containing regimens, the complete response rate (48.3% vs. 30.4%, p=0.033) and very good partial response or better rate (74.1% vs. 57.0%, p=0.038) of VDD were significantly higher than those of VD subgroup. While no superior survival was found between VDD and VD subgroup. In vindesine-containing regimens, no statistically significance was identified between vDD and vAD in terms of response rate and survival. The occurrence rates of all cardiac AEs were similar between VDD and VD. Conclusions: The vDD regimen is similar with vAD in aspect of response rate, survival, and toxicity in NDMM patients. The addition of PLD to VD brings deeper response without increased toxicity, while no superior survival was found.